Eficiência dos hospitais universitários federais no contexto da pandemia do SARS-COV-2 - Dantas, Samilla Ferreira (2023)
In March 2020, the World Health Organization (WHO) announced a public health emergency of international concern, with the rapid spread around the globe of the disease named COVID-19 and defined as a pandemic. The Federal Teaching Hospitals participate in this context as organizations that serve society in the middle of the pandemic period related to the SARS-CoV-2 virus. Added to this, the inputs used in the hospital context are finite, imposing a limit to the number of patients that can be treated. In any period, including during the pandemic, the best use of these inputs is essential, so that it becomes important to evaluate the efficiency of institutions, which can maximize results and minimize the consumption of resources. To do this, the technique of data envelopment analysis (DEA) was used to calculate the relative efficiency of these institutions from 2019 to 2021 and the Malmquist Productivity Index (DEA/IPM) was used to identify the efficiency gains and losses. Cluster analysis was also performed to group HUs according to efficiency scores, size, and geographic region. The results show that the sampled hospitals gained efficiency during the pandemic, meaning that there was no impact on efficiency in general. It is also possible to verify that the number of hospitals with high inefficiency fell from 14 to 2 over the three-year period. The variable with the greatest potential for improvement is the permanence index, which remained as a reference during the three years of the study. The region considered most efficient during the years 2019 and 2020 is the Midwest Region and in the year 2021 is the North Region. It was also ratified that small hospitals are more efficient than large hospitals. The analysis of the triennial average considered that hospitals with their own management are more efficient than those with EBSERH management. It is also noted that there was an increase in production efficiency between the analyzed biennium (2019/2020) and (2020/2021). The cluster analysis allowed identifying that the greatest productivity gain in the years 2020 and 2020 belongs to hospitals in the Norderte and predominantly from the EBSERH management.